A masculine housewife with taste; Austrian traveller Ida Pfeiffer in the Netherlands East Indies (1851-1853) - Honings, Rick (Wacana, Journal of the Humanities of Indonesia, 2024)
In the spring of 1851, Austrian traveller and writer Ida Laura Pfeiffer (1797-1858) embarked on her second trip around the world. Her overseas travels also took her to the Netherlands East Indies (now Indonesia): to Borneo (now Kalimantan), Java, Sumatra, and Celenbes (now Sulawesi). She described her experiences in her book Mijne tweede reis rondom de wereld (1856b), the Dutch translation of her German book Meine zweite Weltreise (1856a, ‘My second world tour’). In the last decades, much has been written about the perspective of female travel authors. On the one hand, nineteenth-century Western women travellers were curtailed because of their womanhood, yet they also played a role in the colonial system. While this might have been “different” compared to that of men, they judged the non-white “Other” in equal measure. This article focuses on how Pfeiffer positions herself in her travel texts. Although she adopts elements of the masculine hero narrative, her book also harbours aspects characteristic of her feminine view.